Gas Expansion Energy Model and Numerical Simulation of Outburst Coal Seam under Multifield Coupling - Jie Cao; Qianting Hu; Yanan Gao; Minghui Li; Dongling Sun (Geofluids)
Due to the insufficient understanding of the outburst mechanism, the coal and gas outburst disasters in China are more serious. Gas expansion energy is the main source of energy that causes outburst. In order to explore the distribution law of gas expansion energy in outburst coal seams, a gas-solid coupling equation of outburst coal seams was established. The distribution law of coal stress field, deformation field, gas flow field, and gas expansion energy were simulated and analyzed by using COMSOL Multiphysics. The results showed that from the excavation face to the deep part of coal seam, the stress presented unloading zone, stress concentration zone, and original stress zone. The volumetric strain and permeability reached the minimum, while the gas pressure reached the maximum at the peak value of vertical stress. As time goes on, the gas pressure in the fracture near the working face gradually decreased and was less than the pressure in coal matrix. The total gas expansion energy consists of free gas and desorption gas expansion energy. Affected by the excavation, free gas expansion energy maintained a constant value in the original coal seam and gradually decreased in the area close to the working face. The expansion energy provided by desorption gas was zero in the original coal seam. And it first increased and then decreased rapidly near the working face. Compared with stress and coal seam thickness, gas pressure and initial diffusion coefficient had significant influence on gas expansion energy of coal seam. When the diffusion coefficient was greater than 1e-9 m2/s, the gas expansion energy of the coal seam near the working face was significantly higher than that of the original coal seam, which had the risk of inducing outburst.